ChemInform Abstract: C—H Arylation of Benzoquinone in Water Through Aniline Activation: Synergistic Effect of Graphite‐Supported Copper Oxide Nanoparticles. Issue 33 (25th July 2013) - Honraedt, Aurelien; Le Callonnec, Francois; Le Grognec, Erwan; Fernandez, Vincent; Felpin, Francois‐Xavier
Abstract This is the first Meerwein arylation under heterogeneous catalysis.